2021
DOI: 10.1177/08862605211050090
|View full text |Cite
|
Sign up to set email alerts
|

Within-Individual Effects of Dropping out of School on Violent Victimization Among Serious Adolescent Offenders

Abstract: Despite a recent decrease in both school dropout and victimization rates, many harsh and exclusionary school policies continue to push school-aged adolescents out of school. This study combines two research areas—school dropout and violent victimization—by investigating if dropping out of school increases the chance of violent victimization. It is hypothesized that a change in the opportunity structure associated with risky lifestyles and routine activities accounts for the link between school dropout and viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Added to this is the fact that adolescent offenders usually have high dropout rates which is often related to a disadvantaged environment, as is the case of the sample of this study with 87.1%. Studies such as Na (2022) found that school dropout can lead adolescents to violent victimization because it can change life opportunities and lead them to risky lifestyles. It should also be taken into account that not all adolescent offenders who are serving their sentences complete their schooling in detention centers.…”
Section: Discussionmentioning
confidence: 99%
“…Added to this is the fact that adolescent offenders usually have high dropout rates which is often related to a disadvantaged environment, as is the case of the sample of this study with 87.1%. Studies such as Na (2022) found that school dropout can lead adolescents to violent victimization because it can change life opportunities and lead them to risky lifestyles. It should also be taken into account that not all adolescent offenders who are serving their sentences complete their schooling in detention centers.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, adolescent offenders confront substantial educational issues, including poor academic performance, dropout, and limited access to suitable educational opportunities [11]. Furthermore, these adolescents could encounter additional societal obstacles, Data 2023, 8, 174 2 of 15 including racial and ethnic bias, domestic instability, and exposure to community violence.…”
Section: Introductionmentioning
confidence: 99%